The Appropriate Use of Employment At-Will in County Sheriffs' Departments: Employment At-Will or Political Patronage?. (September 2014) - Goodman, Doug; French, P. Edward; Neaves, Tonya T.
This study reports survey results of one state's county sheriffs' experiences and attitudes toward employment at will (EAW). We developed a model that tests survey respondents' attitudes concerning when political interference in the employment process is permissible and when it is prohibited. We find that sheriffs who agree on the "spoils-system" uses of EAW have stronger agreement on when political terminations are permissible and when they are not. Sheriffs who inform job applicants that their employment is at will are knowledgeable about when political appointments and terminations are appropriate and when they are not. County sheriffs who terminate employees for politically based reasons misunderstand when political appointments and terminations are prohibited under EAW principles. We conclude with recommendations for public officials who work in EAW environments to avoid liability associated with EAW.